2011
DOI: 10.1097/prs.0b013e318205f3ac
|View full text |Cite
|
Sign up to set email alerts
|

Is Presurgical Nasoalveolar Molding Therapy More Effective in Unilateral or Bilateral Cleft Lip–Cleft Palate Patients?

Abstract: There are differences in efficacy between unilateral and bilateral cleft lip–cleft palate patients undergoing nasoalveolar molding. Understanding these differences may help physicians and dentists better shape expectations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 12 publications
0
18
0
1
Order By: Relevance
“…18,19,36,42 NAM has shown us that targeted forces applied to the nasal cartilage during the neonatal period can lead to a normalization of the nasal anatomy. 42 This study does not call into question NAM’s efficacy; however, this efficacy is reliant on compliance with a strict follow-up schedule, which is not practical in all instances. Therefore, in this study, patients who had undergone NAM were excluded from the study population.…”
Section: Discussionmentioning
confidence: 99%
“…18,19,36,42 NAM has shown us that targeted forces applied to the nasal cartilage during the neonatal period can lead to a normalization of the nasal anatomy. 42 This study does not call into question NAM’s efficacy; however, this efficacy is reliant on compliance with a strict follow-up schedule, which is not practical in all instances. Therefore, in this study, patients who had undergone NAM were excluded from the study population.…”
Section: Discussionmentioning
confidence: 99%
“…, Nazarian Mobin et al . , Simanca et al . , Abbot & Meara ) – even in the long term (Barillas et al .…”
Section: Introductionmentioning
confidence: 99%
“…The presurgical nasoalveolar molding (NAM) technique proposed by Grayson 6 has been gaining popularity over the last two decades due to its utility in reducing the severity of the of clefts in early infancy. 7 Although multiple short-term studies, [8][9][10][11][12] have shown an increase in the columella length, molding of the deformed nasal cartilages, and obtaining arch approximation, the retention of the results obtained have not been conclusively established. 1 We have conducted this longitudinal study to ascertain the 5-year stability of the nasal symmetry achieved by NAM in unilateral cleft lip and palate (UCLP) patients.…”
Section: Introductionmentioning
confidence: 99%